A treasury of Spurgeon on the life and work of our Lord ; v. 4 - Spurgeon, Charles Haddon, 1834-1892 (Grand Rapids, MI Baker, 1979)
Contents : v. 4 : The miracles of our Lord ; pt 1
Keywords: Jesus Christ -- miracles